2014
DOI: 10.1371/journal.pone.0114726
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Phospholipase A2 Protects against Acetaminophen-Induced Acute Liver Injury by Modulating Regulatory T Cells and IL-10 in Mice

Abstract: The aim of this study was to investigate the protective effects of phospholipase A2 (PLA2) from bee venom against acetaminophen-induced hepatotoxicity through CD4+CD25+Foxp3+ T cells (Treg) in mice. Acetaminophen (APAP) is a widely used antipyretic and analgesic, but an acute or cumulative overdose of acetaminophen can cause severe hepatic failure. Tregs have been reported to possess protective effects in various liver diseases and kidney toxicity. We previously found that bee venom strongly increased the Treg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 49 publications
0
45
1
Order By: Relevance
“…However, our previous study has shown that BV has a beneficial role in reliving oxaliplatin-induced neuropathic pain symptoms in rats, suggesting that BV could be an alternative therapeutic option for the management of oxaliplatin-induced peripheral neuropathy [ 9 , 16 ]. Interestingly, we recently found that bvPLA 2 mitigates cisplatin-induced nephrotoxicity and acetaminophen-induced hepatotoxicity, which was more potent than BV [ 24 , 38 ]. In the present study, we investigated for the first time whether bvPLA 2 has an analgesic effect on oxaliplain-induced cold and mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our previous study has shown that BV has a beneficial role in reliving oxaliplatin-induced neuropathic pain symptoms in rats, suggesting that BV could be an alternative therapeutic option for the management of oxaliplatin-induced peripheral neuropathy [ 9 , 16 ]. Interestingly, we recently found that bvPLA 2 mitigates cisplatin-induced nephrotoxicity and acetaminophen-induced hepatotoxicity, which was more potent than BV [ 24 , 38 ]. In the present study, we investigated for the first time whether bvPLA 2 has an analgesic effect on oxaliplain-induced cold and mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…The major pathway of the bvPLA 2 -induced immune modulation is to increase peripheral regulatory T cells, which play a key role in the maintenance of tolerance in the immune system. Our recent studies showed that such strategies using bvPLA 2 could be successful in the prevention of cisplatin-induced acute kidney and acetaminophen-induced acute liver injury, by suppressing immune response via the modulation of regulatory T cells [ 24 , 38 ]. Another previous study also demonstrated that regulatory T cells attenuate peripheral nerve injury-induced neuropathic pain in rats [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bee venom group III sPLA 2 can exert protective effects on airway inflammation via Treg cells in the mouse model of asthma [ 77 ]. Anti-inflammatory effects of bee venom group III sPLA 2 have been demonstrated in cisplatin-induced renal injury and acetaminophen-induced liver injury [ 59 , 78 ]. These protective effects of bee venom group III sPLA 2 against drug-induced organ toxicity are mediated by IL-10 production and Treg cell modulation.…”
Section: Bee Venom Group III Spla 2 : Today’s Fmentioning
confidence: 99%
“…Kim et al demonstrated that PLA2 protects against hepatic dysfunction and induces anti-inflammatory cytokine production in acetaminophen-injected mice. This study suggests that PLA2 may have therapeutic potential in preventing acetaminophen-induced hepatotoxicity [ 60 ].…”
Section: Anti-inflammatory Effect Of Bee Venom On Liver Fibrosismentioning
confidence: 99%